Downregulated spinal IRF8 and BDNF in NAC are involved in neuropathic pain-induced depression relief via pulsed radiofrequency on dorsal root ganglion in rat SNI model - Fang, Xiangyu; Xu, Xueru; Lin, Xingwu; Liu, Rongguo (Brain research bulletin, 2019)
•Activation of IRF8 was involved in the development of pain-induced depression.•Intrathecal injection of IRF8 decreased IRF8 in the spinal cord and BDNF in NAc.•PRF on DRG decreased IRF8 in the spinal cord and BDNF in NAc.•PRF on DRG contributed to attenuate of the neuropathic pain-induced depression. Pulsed radiofrequency (PRF) on the dorsal root ganglion (DRG), which produces remarkable analgesia through high-frequency electromagnetic energy, has become a main therapy for chronic neuropathic pain. The chronic neuropathic pain in patients is frequently accompanied by depression. However, the underlying neurophysiological mechanisms of the treatment of PRF on DRG for the neuropathic pain-induced depression remain unclear. This study was designed to explore the effect of PRF on DRG on the neuropathic pain-induced depression in rats with spared nerve injury (SNI). Here, we found that PRF on DRG or intrathecal injection of the interferon regulatory factor 8 (IRF8) siRNA prevented the increase of mechanical allodynia and depression-like behaviors of rats after receiving SNI. Meanwhile, Western blot, immunohistochemistry, and RT-PCR revealed that PRF on DRG or intrathecal injection of IRF8 siRNA inhibited IRF8 overexpression in the spinal cord and brain-derived neurotrophic factor (BDNF) in NAc. These results suggest that neuropathic pain-induced depression could be attenuated by PRF applied to DRG in SNI rats. The suppressed overexpression of the spinal IRF8 and BDNF in NAc may play an important role and contribute considerably to effectiveness of the therapy by PRF on DRG.